A critical review of South Africa' future carbon tax regime - Hughes, Rebekah (Institute of Marine and Environmental Law, 2017)
The world is currently facing a global climate crisis largely associated with growing greenhouse gas emissions, of which carbon dioxide (CO₂) emissions are a significant component. As the fourteenth largest emitter of CO₂ globally and the highest per capita CO₂ emitter in Africa, South Africa has a responsibility to implement legal and fiscal instruments to reduce its emissions. One instrument receiving growing global attention to reduce CO₂ emissions is carbon tax; a tax imposed directly on the emission of carbon or the use of products which generate carbon emissions. South Africa is following the global trend and has for the past decade sought to formulate a carbon tax regime which is effective in its operation, equitable in its impact across different sectors, and which does not result in the collapse of the country's economy. Whilst yet to be finalised, several policy documents have provided a clear indication of its anticipated form, and 2015 saw the publication of the Draft Carbon Tax Bill with the Bill being re-released in 2017, which by all accounts is due to be finalised for implementation in mid-2017. The time would accordingly appear ripe to critically review the country's anticipated carbon tax regime, and this forms the focus of this dissertation. This critical review was undertaken against several tax design elements identified by international commentators, namely: environmental effectiveness; tax revenue; support for the tax; legislative aspects; technical and administrative viability; competitiveness effects; distributional aspects and adjoining policy areas. The critical analysis of South Africa's imminent carbon tax regime against generally accepted tax elements has determined that it will be effective in its operation, equitable in its impact across different sectors and it will promote a more sustainable and resilient domestic economy.